Exercise habits in adolescence and old age are positively associated with geriatric depressive symptoms: the Bunkyo Health Study - Shi, Huicong; Tabata, Hiroki; Otsuka, Hikaru; Kaga, Hideyoshi; Someya, Yuki; Abudurezake, Abulaiti; Kakehi, Saori; Naito, Hitoshi; Ito, Naoaki; Tajima, Tsubasa; Yoshizawa, Yasuyo; Kawamori, Ryuzo; et al. (Frontiers in Public Health, 2024)
IntroductionExercise is a crucial method for preventing geriatric depression. In this cross-sectional study, we investigated the associations between exercise habits in adolescence and old age and geriatric depressive symptoms.MethodsThis study used baseline data from the Bunkyo Health Study, a prospective observational cohort study investigating the preventive effects of physical activity on causative diseases requiring long-term care. This analysis included 1,629 older adults (687 men and 942 women) aged 65–84 years who participated in the Bunkyo Health Study. Participants were divided into four groups according to their exercise habits in adolescence and old age: never exercised (none-none; NN), exercised only in old age (none-active; NA), exercised only in adolescence (active-none; AN), and exercised in adolescence and old age (active-active; AA). Geriatric depressive symptoms were defined as the short version of the Geriatric Depression Scale score ≥ 5, including depression tendency. Multivariate-adjusted logistic regression models were used to estimate the odds ratios (ORs) and associated 95% confidence intervals in each group for the prevalence of geriatric depressive symptoms compared with the NN group.ResultsThe ORs for geriatric depressive symptoms were notably lower in the AN, NA, and AA groups than in the NN group in both older men and older women.ConclusionThese results indicate that older adults with exercise habits in adolescence and/or in old age exhibit a lower prevalence of geriatric depressive symptoms.